Hubungan Antar agama - Muchlis Muhammad Hanafi (SUHUF, 2008)
This writing studies "standing position" of Islam among other Divine Religions (Agama Samawi) such as Jews and Christianity. Islam is the substance of the teachings revealed to some prophets before the Prophet Muhammad, and Muhammad is considered to be the seal of the prophethood. Therefore, the dialogue to be conducted among those Divine Religions such as the dialogue with Jews and Christianity requires that both Jews and Christianity go back to their original teachings and forms, before both have gone through the changes for the reasons of time and human intervention. It is without that requirement, the dialogue being conducted among Divine Religions will never come to an agreement to the meeting point.